Pengaruh Motivasi Kerja dan Disiplin Kerja terhadap Produktivitas Kerja Karyawan Bagian Sortir PT. Lestari Mahaputra Buana - Pani Apriliani; Aam Rachmat Mulyana (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to determine the effect of work motivation and work discipline on the work productivity of sorting department employees at PT Lestari Mahaputra Buana. The research method used is a quantitative method with a literature study approach and field study through questionnaires, interviews, and documentation. The population and sample in this study were all sorting department employees totaling 34 people. The data obtained were analyzed using validity, reliability, normality, multicollinearity, heteroscedasticity, multiple linear regression, t-test, and f-test. The results showed that the research instrument was valid and reliable. The regression test showed that partially work motivation did not have a significant effect on work productivity (t count = 0.029; sig = 0.977> 0.05), while work discipline had a significant effect (t count = 5.069; sig = 0.000 <0.05). Simultaneously, work motivation and work discipline together have a significant effect on work productivity (Fcount = 13.804; sig = 0.000 <0.05) with a coefficient of determination of 47.1%. The conclusion of this study is that work productivity is significantly influenced by work discipline, while work motivation does not provide a significant effect partially. Keywords: Work Motivation, Work Discipline, Work Productivity